Figuring out the Eighties - 80s. (Newcastle : Laing Art Gallery, 1988)
Arif, Saleem ; Booker, Alex ; Cooper, Eileen ; Coventry, Keith ; Crowley, Graham ; Dennis, Jeffrey ; Forrester, Denzil ; Jones, Tim ; Lansley, Erica Faith ; Leapman, David ; Redfern, June ; Stahl, Andrew ; Treister, Suzanne
Figuring out the Eighties - 80s, Laing Art Gallery, Newcastle, 16 june - 24 july 1988
boek